1992
DOI: 10.1182/blood.v80.3.816.bloodjournal803816
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hemoglobin levels in sickle cell disease and normal individuals are partially controlled by an X-linked gene located at Xp22.2

Abstract: Fetal hemoglobin (Hb F) production in sickle cell (SS) disease and in normal individuals varies over a 20-fold range and is under genetic control. Previous studies suggested that variant Hb F levels might be controlled by genetic loci separate from the beta-globin complex on chromosome 11. Using microscopic radial immunodiffusion and flow cytometric immunofluorescent assays to determine the percentage of F reticulocytes and F cells in SS and nonanemic individuals, we observed that F-cell levels were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 28 publications
5
47
2
Order By: Relevance
“…In addition, our results have either been generated by a single observer using a single machine at UWI or, where results from another laboratory (at KCL) were incorporated into our analyses, we have explicitly assessed the agreement between the two sites. Previous studies that suggested ethnic differences in HbF and FC levels have either used techniques such as alkaline denaturation or immunofluorescence blood smears Wood et al, 1975) or have used flow cytometry on smaller numbers of participants (Dover et al, 1992). Our relatively large study using flow cytometry has now confirmed and extended the notion that there are important differences between ethnic groups for FC levels.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, our results have either been generated by a single observer using a single machine at UWI or, where results from another laboratory (at KCL) were incorporated into our analyses, we have explicitly assessed the agreement between the two sites. Previous studies that suggested ethnic differences in HbF and FC levels have either used techniques such as alkaline denaturation or immunofluorescence blood smears Wood et al, 1975) or have used flow cytometry on smaller numbers of participants (Dover et al, 1992). Our relatively large study using flow cytometry has now confirmed and extended the notion that there are important differences between ethnic groups for FC levels.…”
Section: Discussionsupporting
confidence: 69%
“…The presence of an X-linked QTL was suggested by surveys in different population groups, which clearly confirmed that adult females have higher HbF and FC values than males (Rutland et al, 1983;Sampietro et al, 1992;Thein & Craig, 1998). Miyoshi et al (1988) and Dover et al (1992) argued for the existence of a locus on the X chromosome which at least partially controls FC production in an X-linked dominant fashion. Analysis of F-reticulocytes (reticulocytes containing measurable HbF) in male and female sickle cell patients, and sib-pair studies from the same population suggested a co-dominant FC production (FCP) locus on chromosome Xp22AE2-22AE3 (Dover et al, 1992).…”
Section: Evidence For Other Qtls?mentioning
confidence: 71%
“…Miyoshi et al (1988) and Dover et al (1992) argued for the existence of a locus on the X chromosome which at least partially controls FC production in an X-linked dominant fashion. Analysis of F-reticulocytes (reticulocytes containing measurable HbF) in male and female sickle cell patients, and sib-pair studies from the same population suggested a co-dominant FC production (FCP) locus on chromosome Xp22AE2-22AE3 (Dover et al, 1992). Both the chromosome 8-and X-linked QTLs have not been validated in subsequent genomewide linkage and association studies (Craig et al, 1996;Menzel et al, 2007a;Uda et al, 2008).…”
Section: Evidence For Other Qtls?mentioning
confidence: 99%
“…Among patients with sickle cell anaemia, HbF concentrations vary from 0AE1% to 30% with an average of about 8%. Understanding why patients' HbF levels differ so substantially (Dover et al, 1987(Dover et al, , 1992Chang et al, 1995Chang et al, , 1997Garner et al, 1998Garner et al, , 2002Ofori-Acquah et al, 2004;Wyszynski et al, 2004a) may help us to devise better therapeutics to induce HbF (c-globin gene; HBG1, HBG2) expression, a goal of b-haemoglobinopathy treatment. Unfortunately, knowing the HbF level of an individual is insufficient to foretell the likely complications.…”
Section: Fetal Haemoglobinmentioning
confidence: 99%